Negative Allosteric Modulators Selective for The NR2B Subtype of The NMDA Receptor Impair Cognition in Multiple Domains - Weed, Michael R (Neuropsychopharmacology, 2016)
Antidepressant activity of N-methyl-D-aspartate (NMDA) receptor antagonists and negative allosteric modulators (NAMs) has led to increased investigation of their behavioral pharmacology. NMDA antagonists, such as ketamine, impair cognition in multiple species and in multiple cognitive domains. However, studies with NR2B subtype-selective NAMs have reported mixed results in rodents including increased impulsivity, no effect on cognition, impairment or even improvement of some cognitive tasks. To date, the effects of NR2B-selective NAMs on cognitive tests have not been reported in nonhuman primates. The current study evaluated two selective NR2B NAMs, CP101,606 and BMT-108908, along with the nonselective NMDA antagonists, ketamine and AZD6765, in the nonhuman primate Cambridge Neuropsychological Test Automated Battery (CANTAB) list-based delayed match to sample (list-DMS) task. Ketamine and the two NMDA NR2B NAMs produced selective impairments in memory in the list-DMS task. AZD6765 impaired performance in a non-specific manner. In a separate cohort, CP101,606 impaired performance of the nonhuman primate CANTAB visuo-spatial Paired Associates Learning (vsPAL) task with a selective impairment at more difficult conditions. The results of these studies clearly show that systemic administration of a selective NR2B NAM can cause transient cognitive impairment in multiple cognitive domains.